Biological spectrum and phytogeographical patterns of endemic and near-endemic plants in Abyan Governorate, Yemen - MADLEEN A. OBEL; GHALIA S. ALJEDDANI; ZAMILA M. MASDOOS; MOHAMMED A. HUSSEIN; ABDUL WALI A. AL-KHULAIDI; ABDUL-NASSER AL-GIFRI; IMAN H. NOUR (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Obel MA, Aljeddani GS, Masdoos ZM, Hussein MA, Al-Khulaidi AWA, Al-Gifri AN, Nour IH. 2026. Biological spectrum and phytogeographical patterns of endemic and near-endemic plants in Abyan Governorate, Yemen. Biodiversitas 27 (3): d270329. https://doi.org/10.13057/biodiv/d270329. Yemen faces serious biodiversity challenges; documenting endemic and near-endemic taxa supports its strategic conservation goals. This study reports and catalogs the endemic and near-endemic plant species in Abyan, emphasizing their life forms, life spans, growth forms, and phytogeography. Vegetation surveys were conducted for two successive spring seasons in 2023 and 2024. The field survey used a timed exploratory meander technique using non-plot sampling to maximize detection of taxa in inaccessible areas of the study site. Eight mountain peaks were selected to reflect the geographic extent of the study region. Fifty-seven endemic and near-endemic taxa, representing 21 plant families, were recorded, of which 23 are endemic and 34 are near-endemic. Aloe serriyensis, Kleinia deflersii, and Stapelia × anemoniflora are endemic to Jabal Al-Arays, located in the Khanfir District of Abyan. The floristic study revealed that Apocynaceae and Asteraceae were the most abundant families. Forty-one genera were recorded, with Aloe being the most species-rich genus. Perennial plants were more abundant than annuals in the study area, reflecting their greater tolerance to arid conditions. Subshrubs represented the dominant growth form, surpassing trees, shrubs, and herbs. Among the five identified life forms, chamaephytes were the most dominant. Phytogeographically, the Sudano-Zambezian chorotype accounts for more taxa than the Saharo-Arabian/Sudano-Zambezian, which is consistent with Yemen's geography and best represents hot desert habitats. Jabal Al-Arays comprises 57.9% of the total recorded taxa, including 13 near-threatened taxa and 1 critically endangered species. Thus, an urgent conservation plan should be implemented in Jabal Al-Arays through habitat protection and grazing control to safeguard endemic taxa under threat. Sustaining mountain biodiversity under increasing anthropogenic pressures and climatic change will require coordinated efforts among scientists, the governmental sector, and local communities, supported by predictive modeling to anticipate future biodiversity loss at high elevations in the coming decades.